Susceptibilities of Mycoplasma gallisepticum and Mycoplasma synoviea Isolates to Antimicrobial Agents in vitro - Behbahan, N. Ghaleh Golab; Asasi, K.; Afsharifar, A.R.; Pourbakhsh, S.A. (International Journal of Poultry Science, 2008)
The in vitro activities of aivlosin tylosin tiamulin, erythromycin, oxytetracycline, spectinomycin, lincomycin, lincomycin-spectinomycin (1:2) and enrofloxacin were determined against twenty-eight isolates of Mycoplasma gallisepticum and 4 isolates of Mycoplasma synoviae using microbroth dilution method. The isolates showed various susceptibilities to antimicrobial agents. Aivlosin, lincomycin-spectinomycin (1:2), tylosin, tiamulin, enrofloxacin and also lincomycin were commonly more effective against these field isolates. However, aivlosin was the most effective drugs against Mycoplasma gallisepticum and Mycoplasma synoviae as its MIC was the lowest of all. Oxytetracycline, erythromycin and spectinomycin were not effective against all isolates, as their MICs for some of isolates were extremely high. The MIC of erythromycin and oxytetracycline were distributed across a broad range. Resistant strains to two mentioned antibiotics were obtained from the field.